Printable microfluidic systems using pressure sensitive adhesive material for biosensing devices - Wang, Xin; Nilsson, David; Norberg, Petronella (Biochimica et biophysica acta, 2013)
In biosensors with a fluid analyte, the integration of a microfluidic system, which guides the analyte into the sensing area, is critical. Quicker and economical ways to build up microfluidic systems will make point of care diagnostics viable. Printing is a low-cost technology that is increasingly used in emerging organic and flexible electronics and biosensors. In this paper, we present printed fluidic systems on flexible substrates made with pressure sensitive adhesive materials. Printable pressure sensitive adhesive materials have been used for making microfluidic systems. Flexible substrates have been used, and two types of adhesive materials, one thermally dried and another UV curable, have been tested. Top sealing layer was laminated directly on top of the printed microfluidic structure. Flow tests were done with deionized water. Flow tests with deionized water show that both adhesive materials are suitable for capillary flow driven fluidic devices. Flow test using water as dielectric material was also done successfully on a printed electrolyte gated organic field effect transistor with an integrated microfluidic system. Due to its ease of process and low cost, printed microfluidic system is believed to find more applications in biosensing devices. This article is part of a Special Issue entitled Organic Bioelectronics—Novel Applications in Biomedicine. ► Pressure sensitive adhesive materials were screen printed to make fluidic systems. ► Flow tests on printed microfluidic systems were successfully conducted. ► Our printed microfluidic system is easy to scale up and cost-effective.